Text Sociology in the Novel, Zakirat Al-Jasad by Ahlam Mosteghanemi - fateme akbarizade; Kobra Roshan Fekr; Khalil Parvini; Hosseinali Ghobadi (دراسات في اللغة العربيّة وآدابها)
Based on the framework of text sociology, the structure of the novel itself indicates the narrative and dialogical structure as well as the ideational content. So, the textual analysis of a novel is done based on internal analysis of texts and without relying on external facts and events. In the aesthetic application of this critical approach, it is seen that the available dialogic relations in the novel as a community produce an ideological orientation in the textual population so that there is either a democratic and polyphonic situation or a dominant ideology and a monologist novel. The Algerian novelist, Ahlam Mosteghanemi, in her novel, Zakirat Al-Jasad, has a special approach in which the reader cannot easily tell apart the monologue from polyphony. Thus, taking a descriptive-analytic approach, this study studied the dialogic style of this novel at three levels: representational methods, the realization of the presence of the narrator and the narrative pronouns, and the ideological perspective. The results show this feminine writing has various narrative pronouns and middle style âneither bias nor neutral-- in representing the statements of characters it also narrates different ideological views about women and land. The outcome of the ideological approach is a polyphonic novel in both cases. The possibility of text interpretation for reader and its open- endedness can mean that this feminine writing is not monologist anymore and contrary to the belief of those who consider feminine writing merely monologist, this novel tends to be polyphonic.